Aleksandr Deineka’s Works in the Context of the Art Deco Style - A. S. Dobrydneva (Концепт: философия, религия, культура, 2020)
This paper analyzes the founding bases of comparisons between the Aleksandr Deineka’s artistic works and the art deco, the connection between Deineka’s works and European and American art of the 1930s Deineka’s early works refer to the avant-garde and the late ones are usually related to socialist realism. The novel artistic language is the most important link between the Soviet art and the art deco style, making the artist its most prominent USSR proponent. In this respect, the key event is the artist’s trip to the USA, France and Italy in 1935. What made Deineka engage in the intercultural discussion on artistic styles were industrial, urban, mundane and sport themes the Soviet art and art deco (mostly American) shared. A dialogue with the US Skyscraper style influenced a series of paintings and sketches, including New York. Central Park, The Road to Mount Vernon, Baseball, The Boredom. The Soviet experience contributed to Deineka’s few American works. In the most clear and general manner the art deco ideas and practical solutions were incorporated in the 1938 project of Deineka – in the decoration of the Mayakovskaya metro station, Moscow. The idea was to create a series of allegoric and technically new mosaic plafonds. Both spirit and techniques of late Deineka were partly inspired by the American art deco.